Morphology and dynamics of carbon nanotube in polycarbonate carbon nanotube composite from dissipative particle dynamics simulation - Chakraborty, Souvik; Choudhury, Chandan Kumar; Roy, Sudip (Macromolecules, 2013)
Morphology and dynamics of carbon nanotube (CNT) in polycarbonate matrix with different mixing ratios are studied in mesoscale by using dissipative particle dynamics (DPD). We have used atomistic simulation to derive necessary interaction parameter for mesoscale DPD simulation for polycarbonate nanotube composite using Flory-Huggins theory. The diffusion and morphology of nanotubes in different concentrations (2%, 5%, 10%) are investigated. Diffusivity of nano tubes in polymer matrices is explored at different temporal regimes of simulation. Diffusion of nanotubes becomes significantly slow when bundling of nanotubes takes place. The bundle formation of nanotubes is observed in all of three mixtures with varying degrees of assembling and alignment Bundle size analysis is performed to study the extent of bundling affinity of CNTs in different filler concentrations. Size of the bundles of nanotubes is more in higher nanotube concentrations. In the 10% mixture percolation network is found to be formed by bundles of nanotubes.